ADAPT NXT: Fixed Cycles or Every‐Other‐Week IV Efgartigimod in Generalized Myasthenia Gravis - Ali A. Habib; Kristl G. Claeys; Vera Bril; Yessar Hussain; Kelly Gwathmey; Gregory Sahagian; Elena Cortés‐Vicente; Edward Brauer; Deborah Gelinas; Anne Sumbul; Rosa H. Jimenez; Daniela Hristova; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT Objective This phase 3b, open‐label, randomized ADAPT NXT study investigated the efficacy, safety, and tolerability of efgartigimod administered in either a fixed cycles dosing regimen (3 cycles of 4 once‐weekly infusions, with 4 weeks between cycles) or a cycle followed by every‐other‐week (Q2W) dosing. Methods Adult participants with anti‐acetylcholine receptor antibody‐positive generalized myasthenia gravis (gMG) were randomized 3:1 to Q2W or fixed cycles dosing of efgartigimod (10 mg/kg intravenously) for 21 weeks. The primary endpoint was the mean change from baseline in total Myasthenia Gravis Activities of Daily Living (MG‐ADL) score averaged across 21 weeks. Results Sixty‐nine participants were treated (fixed cycles, n = 17; Q2W, n = 52). Least squares (LS) mean (95% CI) of the change from baseline in MG‐ADL total score from Weeks 1 to 21 was −5.1 (−6.5 to −3.8) in the fixed cycles arm and −4.6 (−5.4 to −3.8) in the Q2W arm. Clinical improvements were observed in MG‐ADL total scores as early as Week 1 and were maintained throughout the study. Achievement of minimal symptom expression (MG‐ADL: 0–1) from Weeks 1 to 21 occurred in 47.1% (n = 8/17) and 44.2% (n = 23/52) of participants in the fixed cycles and Q2W arms, respectively. Efgartigimod was well tolerated; COVID‐19, headache, and upper respiratory tract infection were the most common treatment‐emergent adverse events. Interpretation Efgartigimod administered as either fixed cycles or Q2W dosing results in rapid, robust, and sustained clinically meaningful improvement. These results build upon previous studies and provide additional efgartigimod dosing approaches to achieve and sustain clinical efficacy in patients with gMG.